Colorectal Cancer Screening in the Era of the Affordable Care Act - Richman, Ilana (J Gen Intern Med, 2015)
BACKGROUND: The Affordable Care Act (ACA) eliminated cost-sharing for evidence-based preventive services in an effort to encourage use. OBJECTIVE: To evaluate use of colorectal cancer (CRC) screening in a national population-based sample before and after implementation of the ACA. DESIGN: Repeated cross-sectional analysis of the Medical Expenditure Panel Survey (MEPS) between 2009 and 2012 comparing CRC screening rates before and after implementation of the ACA. PARTICIPANTS: Adults 50–64 with private health insurance and adults 65–75 with Medicare. MAIN MEASURES: Self-reported receipt of screening colonoscopy, sigmoidoscopy, or fecal occult blood test (FOBT) within the past year among those eligible for screening. KEY RESULTS: Our study included 8617 adults aged 50–64 and 3761 adults aged 65–75. MEPS response rates ranged from 58 to 63%. Among adults aged 50–64, 18.9–20.9% received a colonoscopy in the survey year, 0.59–2.1% received a sigmoidoscopy, and 7.9–10.4% received an FOBT. For adults aged 65–75, 23.6–27.7% received a colonoscopy, 1.3–3.2% a sigmoidoscopy, and 13.5–16.4% an FOBT. In adjusted analyses, among participants aged 50–64, there was no increase in yearly rates of colonoscopy (−0.28 percentage points, 95% CI −2.3 to 1.7, p = 0.78), sigmoidoscopy (−1.1%, 95% CI −1.7 to −0.46, p = <0.001), or FOBT (−1.6%, 95% CI −3.2 to −0.03, p = 0.046) post-ACA. For those aged 65–75, rates of colonoscopy (+2.3%, 95% CI −1.4 to 6.0, p = 0.22), sigmoidoscopy (+0.34%, 95% CI 0.88 to 1.6, p = 0.58) and FOBT (−0.65, 95% CI −4.1 to 2.8, p = 0.72) did not increase. Among those aged 65–75 with Medicare and no additional insurance, the use of colonoscopy rose by 12.0% (95% CI 3.3 to 20.8, p = 0.007). Among participants with Medicare living in poverty, colonoscopy use also increased (+5.7%, 95% CI 0.18 to 11.3, p = 0.043). CONCLUSIONS: Eliminating cost-sharing for CRC screening has not resulted in changes in the use of CRC screening services for many Americans, although use may have increased in the post-ACA period among some Medicare beneficiaries. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-015-3504-2) contains supplementary material, which is available to authorized users.